Internationally trained pharmacists in Great Britain: what do registration data tell us about their recruitment? - Hassell Karen; Schafheutle Ellen I (Human Resources for Health, 2009)
Abstract Background Internationally trained health professionals are an important part of the domestic workforce, but little is known about pharmacists who come to work in Great Britain. Recent changes in the registration routes onto the Register of Pharmacists of the Royal Pharmaceutical Society of Great Britain may have affected entries from overseas: reciprocal arrangements for pharmacists from Australia and New Zealand ended in June 2006; 10 new states joined the European Union in 2004 and a further two in 2007, allowing straightforward registration. Aims The aims of the paper are to extend our knowledge about the extent to which Great Britain is relying on the contribution of internationally trained pharmacists and to explore their routes of entry and demographic characteristics and compare them to those of pharmacists trained in Great Britain. Methods The August 2007 Register of Pharmacists provided the main data for analysis. Register extracts between 2002 and 2005 were also explored, allowing longitudinal comparison, and work pattern data from the 2005 Pharmacist Workforce Census were included. Results In 2007, internationally trained pharmacists represented 8.8% of the 43 262 registered pharmacists domiciled in Great Britain. The majority (40.6%) had joined the Register from Europe; 33.6% and 25.8% joined via adjudication and reciprocal arrangements. Until this entry route ended for pharmacists from Australia and New Zealand in 2006, annual numbers of reciprocal pharmacists increased. European pharmacists are younger (mean age 31.7) than reciprocal (40.0) or adjudication pharmacists (43.0), and the percentage of women among European-trained pharmacists is much higher (68%) when compared with British-trained pharmacists (56%). While only 7.1% of pharmacists registered in Great Britain have a London address, this proportion is much higher for European (13.9%), adjudication (19.5%) and reciprocal pharmacists (28.9%). The latter are more likely to work in hospitals than in community pharmacies, and all groups of internationally trained pharmacist are more likely to work full-time than British-trained ones. Adjudication pharmacists appear to stay on the Register longer than their reciprocal and European colleagues. Conclusion Analysis of the Register of Pharmacists provides novel insights into the origins, composition and destinations of internationally trained pharmacists. They represent a notable proportion of the Register, indicating that British employers are relying on their contribution for the delivery of pharmacy services. With the increasing mobility of health care professionals across geographical borders, it will be important to undertake primary research to gain a better understanding of the expectations, plans and experiences of pharmacists entering from outside Great Britain.